The Supportive Role of School Management on The Work Satisfaction of Male Teachers in A South African School District - Dr Paul Triegaardt; Jean-Pierre Hugo (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2020)
The paper focused on a specific research group (male teachers); firstly because of the shortage of male teachers in South African schools, and secondly, because male teachers are more dissatisfied in their overall work environment than female teachers. This study aimed to investigate, from an educational management perspective, the factors that influence job satisfaction amongst male teachers in schools in a sampled school district in Mpumalanga province. Throughout the study, it became apparent that male teachers are more likely to leave the South African education system than their female counterparts. A quantitative research approach was used to investigate factors affecting job satisfaction amongst male teachers distributing Likert-scale questionnaires amongst male teachers in selected schools in the district. The results of the study provide an outline of the crises that teachers in South Africa schools are facing, while the statistics and information portrayed in this study help to paint a picture of their work environment. A shortage of teachers, increasing learner enrolment and work overload are enough to create a highly stressful profession. Aspects identified as factors that affect job satisfaction amongst male teachers are the professional development of teachers, capacity building of teachers through collaboration and teamwork, effective support systems to teachers by management, workload of teachers, effective leadership of the principal, effective management of learner behaviour, positive work experiences by teachers, emotional distress of teachers and positive feelings towards teaching as a profession.